Keeping emerging litchi pests under changing climate at bay - Srivastava, Kuldeep; Srivastava, Kuldeep (Indian Horticulture, 2019)
Litchi (Litchi chinensis Sonn.) is an important subtropical evergreen fruit belongs to family Spindaceae. In increasing tune, country produces 5,80,000 metric tonnes of litchi from 82,700 ha (2012-13) with an average productivity of 7.0 t/ha. Many biotic stresses, particularly insect pests play a vital role in lowering the production and productivity. Additionally, under changing climate, many secondary pests are becoming major threat to quality litchi production. Therefore, an attempt has been made to describe such emerging pests along with probable and advanced management practices to manage litchi pests.